Trends and Patterns of Population Migration: Analytical Study In Indian Context: Understanding the Dynamics of Population Migration in India (Journal of Advances and Scholarly Researches in Allied Education, 2015)
World population grows as a result of births and declinesas a result of deaths. Net migration is the difference between the number ofpeople entering a geographic area (immigrants) and those leaving (emigrants).Over time, migration contributes more than just the initial number of peoplemoving into an area, because the children and grandchildren born to theimmigrant population add several times the original number to the populationbase. There is also an increase in the number of deaths as a result ofin-migration. This paper focused with the trends and patterns of populationmigration.